2021
DOI: 10.1101/2021.01.26.428337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STING agonism enhances anti-tumor immune responses and therapeutic efficacy of PARP inhibition inBRCA-associated breast cancer

Abstract: Poly (ADP-ribose) polymerase (PARP) inhibitors exert their efficacy by inducing synthetic lethal effects, as well as cGAS/STING-mediated immune responses in BRCA- and other homologous recombination repair-deficient cancer cells. Here we investigated whether the immunologic and therapeutic effects of PARP inhibition in BRCA-deficient breast cancer models could be augmented by synthetic cyclic dinucleotide agonists of STING. Combined PARP inhibition and STING agonism induced a greater degree of STING pathway act… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Direct STING agonists have been evaluated in the preclinical setting in combination with PARPi. Preliminary in vitro experiments [26,42] of this combination in BRCA-deficient breast cancer models demonstrated that PARP inhibition and STING agonism can augment STING pathway activation and pro-inflammatory cytokine production along with improved leucocyte and dendritic cell function compared to monotherapy. Clinical evaluation of direct STING agonism with PARP inhibition is not yet underway, but this is likely to change very soon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct STING agonists have been evaluated in the preclinical setting in combination with PARPi. Preliminary in vitro experiments [26,42] of this combination in BRCA-deficient breast cancer models demonstrated that PARP inhibition and STING agonism can augment STING pathway activation and pro-inflammatory cytokine production along with improved leucocyte and dendritic cell function compared to monotherapy. Clinical evaluation of direct STING agonism with PARP inhibition is not yet underway, but this is likely to change very soon.…”
Section: Discussionmentioning
confidence: 99%
“…To explore this potential synergy in detail, we need to review the cGAS/STING pathway which underscores the immunomodulatory effects of PARP inhibitors [26]. The cGAS-c-GAMP-STING pathway is activated when cytosolic DNA is sensed by cyclic GMP-AMP synthase (cGAS).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Rucaparib, for example, is commonly used as a maintenance therapeutic alongside platinum-based chemotherapy (cite 30830551). A January 2021 study found that olaparib treatment coupled with stimulator of interferon genes (STING) agonism induces more significant STING activation than STING agonism alone [81]. By increasing cytotoxic T cell response, this combined therapy improved anti-tumor effects significantly [81].…”
Section: Talazoparibmentioning
confidence: 99%
“…A January 2021 study found that olaparib treatment coupled with stimulator of interferon genes (STING) agonism induces more significant STING activation than STING agonism alone [81]. By increasing cytotoxic T cell response, this combined therapy improved anti-tumor effects significantly [81]. Furthermore, this effect is more significant when also coupled with checkpoint inhibitors that block PD-1 [82].…”
Section: Talazoparibmentioning
confidence: 99%
“…The combination with anti-PDL1 immunotherapy is promising because, as proven in melanoma, cGAMP would activate and recruit CD8 + T cells in the microenvironment, and cGAS seems essential for the success of PD-L1 treatment [ 114 ]. Interestingly, there seems to be immunological synergy between these treatments, and others capable of strongly inducing breaks in DNA, such as PARPi (especially in BRCA-associated BC) [ 115 ].…”
Section: Turning a Non-antigenic And Non-immunogenic “Cold” Bc Tumor Into A “Hot” Tumormentioning
confidence: 99%